One of them days [videorecording (DVD)] - Singleton, Syreeta, 1990-; Palmer, Keke; SZA, 1989-; Calloway, Vanessa Bell, 1957-; Howery, Lil Rel, 1979-; Williams, Katt; Apatow, Maude; Cage, Patrick; Dennis, Gabrielle; James, Janelle; Dancy, Chanda, 1978-; Berkofsky, Ava (Sony Pictures Home Entertainment, 2025)
When best friends and roommates Dreux and Alyssa discover Alyssa's boyfriend has blown their rent money, the duo finds themselves going to extremes in a race against the clock to avoid eviction and keep their friendship intact.